The Legality Of Zakat Blockchain In Indonesia: In the Perspective of Islamic Law and Indonesian Positive Law - Ayu Rahayu Nurhalizah; Sirajul Arifin; Aldi Khusmufa Nur Iman (LAA MAISYIR: Jurnal Ekonomi Islam, 2021)
The amount of zakat funds that must be distributed to mustahiq as well as demands for a guaranteed security system in zakat management become the main focus to attain the goal of zakat management; that is to improve the effectiveness and efficiency of services. Therefore, to attend this goal, blockchain technology is created, which is a digital data storage system consisting of multiservers. This current study explains the legality and validity of zakat blockchain in Indonesia. In collecting data, qualitative approach was employed established in the form of literature review. The techniques of data analysis used were data reduction, data presentation, data triangulation, verification and conclusion of the obtained data. The results indicate that blockchain technology for zakat management is permissible to be used as long as it is not against the Shari’a principles and does not cause mafsadah (harm) or negative consequences. However, regulation that specifies the technology of zakat blockchain in Indonesia is not issued yet, and also some obstacles in its application are still found due to the regions of Indonesian have conditions that are different from one another.